TRADISI UPACARA AMBENGAN ANGGARA KLIWON DI PURA CANDI PENATARAN SABDA UTAMA DESA BARUREJO KABUPATEN BANYUWANGI (KAJIAN NILAI PENDIDIKAN AGAMA HINDU) (JURDIKSCA: Jurnal Pendidikan Agama Hindu Mahasiswa Pascasarjana, 2025)
ABSTRACT The Ambengan Anggara Kliwon tradition which is carried out at the Penataran Sabda main temple in Barurejo village, Banyuwangi regency is an ancestral tradition which is still carried out today and is believed to have deep value. Based on this, the problem can be formulated as follows: 1) What ideology is contained in the Ambengan Anggara Kliwon Ceremonial Tradition at the Penataran Sabda Utama Temple in Barurejo Village, 2) The process of implementing the Ambengan Anggara Kliwon Ceremonial Tradition at the Penataran Sabda Utama Temple in Barurejo Village. 3) The Value of Hindu Religious Education Contained in the Ambengan Anggara Kliwon Ceremonial Tradition at the Penataran Sabda Utama Temple in Barurejo Village. The theory used to study this problem is the author's direction and basis, namely; 1) Religious Theory will be used to answer the question of what ideology is contained in this tradition, 2) Symbolic Interaction Theory will be used to answer the question of how the process of implementing this tradition, 3) Value Theory will be used to answer the question of what value Hindu religious education has. contained in this tradition. This research is a qualitative research. The research process from the data obtained will later produce; 1) What ideology is contained in the Ambengan Anggara Kliwon Ceremonial Tradition at the Pura Candi Penataran Main Sabda Barurejo Village including: Historical Foundations, Religious Foundations, Sociological Foundations. 2) The Process of Implementing the Ambengan Anggara Kliwon Ceremony Tradition at the Penataran Sabda Utama Temple in Barurejo Village includes: Ambengan Anggara Kliwon Facilities and Stages of Implementing Ambengan Anggara Kliwon. 3) The value of Hindu religious education contained in the Ambengan Anggara Kliwon Ceremonial Tradition at the Penataran Sabda Utama Temple in Barurejo Village includes; Tattwa values, ethical values, event values, and harmony values.
Keywords: Keywords: Ambengan Anggara Kliwon, Pitara, Hindu Religious Teachings